Joint-level determinants of the dynamic strength index: implications for testing and monitoring - Ahn, N.; Kim, H.; Krzyszkowski, J.; Roche, S.; Kipp, K. (Sports Biomechanics, 2022)
The aims of this study were to determine the associations and differences between the traditional dynamic strength index (DSIGRF, calculated from ground reaction force [GRF] data) and joint-level dynamic strength indices (DSINJM, calculated from net joint moment [NJM] data). Eight female NCAA Division I lacrosse players performed three maximal effort isometric mid-thigh pulls (IMTP) and countermovement jumps (CMJ). GRF and motion capture data were recorded and used to calculate hip, knee, and ankle NJM. The ratio between peak forces during the IMTP and CMJ tests was used to calculate the DSIGRF and the ratio of peak NJM was used to calculate ankle, knee, and hip DSINJM. Associations and differences between DSIGRF and DSINJM were examined with Pearson`s correlation coefficients, paired t-tests and Hedge`s g effect sizes. The results showed that only the hip DSINJM was correlated with DSIGRF (hip: p = 0.037; r = 0.738). In addition, athletes exhibited significantly greater DSINJM than DSIGRF. Although these results suggest DSIGRF are associated with hip DSINJM, the fact that joint-level DSINJM were generally greater than DSIGRF suggests the ratio between peak NJM during the CMJ and IMTP may not provide intuitive or useful data for strength and conditioning coaches or sport scientists.